Economic Assessment of Producing Corn and Cellulosic Ethanol Mandate on Agricultural Producers and Consumers in the United States. (28th February 2016) - Adusumilli, Naveen C.; Lacewell, Ronald D.; Taylor, C. Robert; Rister, M. Edward
Abstract : Strong support for the biofuels program in the USA is expected to influence dedicated biomass crops production. Their production is expected to compete for resources with traditional crops and in turn influence commodity prices, economic surplus, and trade balance. Implications of dedicated biomass crop as bioenergy feedstock, alternative energy policies, and government initiatives on agricultural producers and consumers are evaluated using a national quantitative model, AGSIM. Economic impacts include effect on cropping patterns, crop prices, fertilizer prices, consumer and producer surplus, and trade balance. Economic analyses based on alternative assumptions related to marginal lands currently in conservation use returning to crop production as well as biomass crop yields are conducted. Results indicate that present biofuel policies are associated with large costs to consumers in terms of increased commodity prices and negative trade balance. Increase in net farm income is offset by decrease in consumer surplus. The results represent a robust set of economic impacts, which suggests policy makers to consider the unexpected economic consequences of bioenergy policy and warrants consideration of multiple alternative energy sources to achieve a sustainable energy goal.